1976
DOI: 10.1017/s0022112076001390
|View full text |Cite
|
Sign up to set email alerts
|

Internal electrohydrodynamic instability and mixing of fluids with orthogonal field and conductivity gradients

Abstract: The interface between two miscible fluids which have identical mechanical properties but disparate electrical conductivities and are stressed by an equilibrium tangential electric field is studied experimentally and theoretically. A bulk-coupled electrohydrodynamic instability associated with the diffusive distribution of fluid conductivity at the interface is experimentally observed.The configuration is modelled using a layer of exponentially varying conductivity spliced on each surface to a constant-conducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
1
1

Year Published

1982
1982
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 3 publications
3
79
1
1
Order By: Relevance
“…An important comparison to this work is the temporal stability analysis of an electrohydrodynamic instability with zero base flow (Hoburg & Melcher 1976, 1977. The mechanism proposed by Hoburg & Melcher is qualitatively similar to that described in figure 17.…”
Section: Mechanism Of Electrokinetic Instabilitymentioning
confidence: 52%
See 2 more Smart Citations
“…An important comparison to this work is the temporal stability analysis of an electrohydrodynamic instability with zero base flow (Hoburg & Melcher 1976, 1977. The mechanism proposed by Hoburg & Melcher is qualitatively similar to that described in figure 17.…”
Section: Mechanism Of Electrokinetic Instabilitymentioning
confidence: 52%
“…The correct internal velocity scale is the electroviscous velocity scale, U ev , which is obtained by balancing viscous and electric stresses. The electroviscous velocity scale is similar to that defined in Hoburg & Melcher (1976) and Melcher (1981). Our definition strives to account for all the relevant physical parameters involved in the electroviscous balance of our problem.…”
Section: Electroviscous Velocitymentioning
confidence: 53%
See 1 more Smart Citation
“…The charge density term ρ e in (3.10) forms in the bulk regions of the flow containing conductivity gradients, and couples with the applied field to generate electrical body forces in the bulk liquid. In a seminal paper on electrohydrodynamic instabilities of so-called 'leaky-dielectrics', Hoburg & Melcher (1976) showed that the accumulation of free charge ρ e in regions of conductivity gradients and collinear applied fields is described by the conservation of the electromigration current (3.4) and Gauss's law (3.5). This coupling can be quantified as…”
Section: Scaling Analysismentioning
confidence: 99%
“…These instabilities are caused by a coupling of electric fields and ionic conductivity gradients that results in an electric body force (per unit volume) of the form ρ e E = ( E · ∇σ )E, where , E and σ are the local permittivity, electric field and ionic conductivity, respectively. In a seminal paper on EHD instability, Hoburg & Melcher (1976) showed that applying electric fields transverse to conductivity gradients in low-conductivity corn oil always results in unstable flows. Baygents & Baldessari (1998) performed a linear stability analysis of fields applied parallel to a linear conductivity gradient in high-conductivity electrolyte solutions.…”
Section: Introductionmentioning
confidence: 99%